Application of X‐ray fluorescence holography to the analysis of the interior and surface of an yttrium oxide thin film. (5th September 2018) - Stellhorn, Jens R.; Hosokawa, Shinya; Happo, Naohisa; Tajiri, Hiroo; Matsushita, Tomohiro; Kaminaga, Kenichi; Fukumura, Tomoteru; Hasegawa, Tetsuya; Kimura, Koji; Hayashi, Kouichi
Abstract : We report on the characterization of a thin film of yttrium oxide by X‐ray fluorescence holography. The sample has a layered structure with an YO base layer and an oxidized Y2 O3 surface. Both layers are clearly observed in the atomic image reconstructions, and their local structure is analyzed. We show that by using incident energies close to the absorption edge of the fluorescing atom, it becomes possible to observe the thin surface layer clearly, even next to a base layer containing the same fluorescing element.